Enabling Food Safety Entrepreneurship: Exploratory Case Studies From Nepal, Senegal, and Ethiopia - Varyvoda, Yevheniia; Cederstrom, Thoric; Borberg, Jenna; Taren, Douglas (Frontiers in Sustainable Food Systems, 2021)
Today, formal and informal enterprises are increasingly contributing to the safety and nutritional ramifications of their food business activities. Enabling entrepreneurship in a sustainable manner means making profits, striving to prevent ingress of harmful substances, and increasing the efficiency of using local natural resources and thus mitigating food hazardous footprints. Using examples from Nepal, Senegal and Ethiopia, this review provides information on microbial and chemical contamination and food adulteration that lead to having unsafe food in the market and on factors that are limiting growing food businesses. Four examples for how to accelerate food safety entrepreneurship are presented that include safely diversifying markets with animal sourced foods, sustainably using neglected and underutilized animal sources, expanding and integrating innovative technologies with traditional practice and using digital technology to improving monitoring and safety along the food supply chain.